The last kingdom. Season two [videorecording (DVD)] - Dreymon, Alexander, 1983-; Dawson, David, 1982-; Santelmann, Tobias, 1980-; Cox, Emily, 1985-; Cornwell, Bernard (Universal Pictures Home Entertainment, 2017)
A story of redemption, vengeance, and self-discovery set against the birth of England, this drama follows young warrior and outsider Uhtred on a fierce mission to reclaim his birthright. The series combines real historical figures and events with fiction, retelling the history of King Alfred the Great and his desire to unite the many separate kingdoms into what would become England.